Operative treatment of avascular necrosis of the femoral head after slipped capital femoral epiphysis - Bartoníček, Jan; Vávra, Jaroslav; Bartoška, Radek (Archives of orthopaedic and trauma surgery, 2011)
PURPOSE: The aim of the study was assessment of the medium-term outcome of operative treatment of avascular necrosis of the femoral head (ANFH) after slipped capital femoral epiphysis (SCFE). MATERIALS AND METHODS: Five patients were treated with valgus-flexion intertrochanteric osteotomy (VFITO) for partial ANFH that developed after operative treatment. Their average age at the time of slip was 12.5 years (range, 10-14); at the time of the reconstructive operation 14 years (range, 12-16), the average interval between slip and the reconstructive operation was 14 months (range, 9-18). Partial ANFH was diagnosed between 6 and 8 months after the slip on the basis of radiographic examination. In all the patients, the anterolateral third up to half of the femoral head was always affected. The average follow-up period was 73 months (range, 60-84). RESULTS: Comparison of MRI scans before and after VFITO proved resorption of the necrotic segment of the femoral head and its remodeling in all the five patients. The average preoperative Harris hip score (HHS) was 86 points, the average postoperative HHS was 94 points. CONCLUSION: VFITO provides a good outcome at medium-term follow-up in adolescent patients with partial ANFH after SCFE.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; Radiography; dítě; osteotomie; radiografie; Child; Female; Hip Joint; Range of Motion, Articular; lidé; Femur Head Necrosis; Epiphyses, Slipped; ženské pohlaví; Male; Adolescent; skluz epifýzy; rozsah kloubních pohybů; mužské pohlaví; nekróza hlavice femuru; Osteotomy; kyčelní kloub; mladiství